Characterization of O-glycan binding lectin from the red alga Hydropuntia eucheumatoides - Dinh Hung, Le; Hai Yen, Tran Thi; Thanh Trung, Dinh (Vietnam Journal of Biotechnology, 2020)
The red alga, Hydropuntia eucheumatoides is one of the algal genera from which agar is commercially extracted, and is the main source of agar in the world. The lectin HEL from the red alga H. eucheumatoides was isolated by a combination of aqueous ethanol extraction, ethanol precipitation, ion exchange and filtration chromatography. Lectin gave a single band with molecular mass of 17,000 Da in both non-reducing and reducing SDS-PAGE conditions, therefore lectin exists in monomeric form. The hemagglutination activities of HEL were stable over a wide range of pH from 3 to 10, temperature up 60 oC and not affected by either the presence of EDTA or addition of divalent cations, indicating that lectin requires no metal for biological activity. The hemagglutination activities of HEL were not inhibited by monosaccharides and glycoproteins, D-glucose, D-mannose, D-galactose, D-xylose, N-acety-D-mannosamine, transferin, fetuin and yeast mannan, but strongly inhibited by monosaccharides containing acetamido groups at equatorial C2 position, such as N-acetyl-galactosamine, N-acetyl-glucosamine, N-acetyl-neuraminic acid and glycoprotein porcine stomach mucin bearing O-glycans. Thus, lectin is specific for O-glycans and may recognize the sequences GalNAcαSer/Thr, GalNAc(α1-3)[Fuc(α1-2)]Gal(β1-4)GlcNAc(β1-3)GalNAc- and GluNAc(α1-4)Gal- under interacting with the acetamido groups at equatorial C2 position of the terminal sugar residues in oligosaccharide structures of O-glycans. The red alga H. eucheumatoides could promise to be a source of valuable lectins for application in biochemistry and biomedicine.